Entre o específico e o indissociável : formação docente e ensino colaborativo para a inclusão escolar - Azevedo, Tereza Hortencia da Silva (2020)
This research aimed to analyze the contributions of collaborative teaching to the educational practice of teachers of the common class and of the multifunctional resource room (SRM), mapping the learning (re) built by these professionals in the formative itinerary of the municipal school. I defend from the idea that collaborative teaching enhances the knowledge, skills, attitudes and values of teachers to the reframing of praxis, with a view to promoting meaningful learning for students with disabilities (AcD). This research is based on the theory of complexity where there is a connection with the object of study that expresses ways of conceiving knowledge and teaching from theoretical-practical changes in favor of a transdisciplinary attitude. As for the nature of the data, it is a qualitative investigation, using secondary sources, such as: books, theses, dissertations, articles, laws, decrees, normative acts, resolutions, reports, as well as documents made available by the school involved. The intervention-research methodology was also adopted in order to monitor the processes related to the pedagogical practices developed by the teachers of the common class and the SRM, applying the method of cartographic procedure to capture the singularities of the movements of attention, namely: tracking, touching, landing and attentive recognition that dialogue and transit among themselves. The locus was a municipal school, located in Aracaju/Sergipe, which has 536 students, 20 of them with disabilities. The staff is composed by two teachers from the Specialized Educational Service (AEE) and 27 from early childhood education to the early years of elementary school. A member from directive staff, 5 common classes teachers, 2 from AEE and 3 techniques from Municipal Secretary of Education. Instruments for data production were field diary, current conversations, educational memories, and semi-structured interview, which were analyzed in the light of sub-signifier notions. The results allowed to identify the difficulties of the teachers in the development of the pedagogical practice in what concerns the AcD, whether these are proportionate, among other factors, to continuing education dissociated from theory and practice. The teachers expressed the importance of interrelation between collaborative teaching and pedagogical praxis in the mediation of the education process for the strengthening of scholar inclusion, where formation appears as an opportunity for reflection-action-reflection among professionals of common classes and the SRM, leading to the reframing of knowledge and different learnings from lived experiences.